Natrarchaeobiusversutus sp. nov. and Natrarchaeobius oligotrophus sp. nov., chitinotrophic natronoarchaea from hypersaline soda lakes, and functional genome analysis of the Natrarchaeobius species - Adolf S. Tulenkov; Adolf S. Tulenkov; Alexander G. Elcheninov; Dimitry Y. Sorokin; Dimitry Y. Sorokin (Frontiers in Microbiology, 2025)
Polysaccharide-degrading natronoarchaea have been poorly studied to date. However, over the past decade, significant progress has been made in understanding their diversity and metabolic potential. In this study, two natronoarchaeal strains, enriched from oxic sediment samples of the soda lakes of Wadi an Natrun in Egypt (AArcel7) and Kulunda steppe in Russia (A-rgal3), were characterized. Strain AArcel7 was enriched with amorphous cellulose, while strain A-rgal3 dominated an enrichment culture using rhamnogalacturonan. Cells of both strains are polymorphic, from motile flat rods to nonmotile cocci. They are aerobic heterotrophs that are able to grow on chitin and several other carbohydrates. Both strains thrive within a salinity range of 2.5 to 4.5 M total Na+, with optimal growth at 3.5–4 M, and are moderately alkaliphilic with an optimum pH at 8.5–9.0 (AArcel7) and 9.2–9.5 (A-rgal3). Genome-based phylogenetic analysis demonstrated that these isolates form a new species lineage in the chitin-specialized genus Natrarchaeobius. An in-depth study of Natrarchaeobius genomes allowed us to identify several genes that potentially enable them to hydrolyze chitin and to metabolize N-acetylglucosamine (GlcNAc), which has not been investigated previously in the chitin-utilizing natronoarchaea. Based on physiological, phylogenetic, and genomic analyses, strains AArcel7 and A-rgal3 are suggested to form a novel species, Natrarchaeobius versutus sp. nov., with AArcel7T (DSM 119357 = UNIQEM U973) as the type strain. Furthermore, strain AArcht7T, formerly classified as the type species of the genus Natrarchaeobius, is proposed to be reclassified as Natrarchaeobius oligotrophus (DSM 119677 = UNIQEM U967).